Antibacterial and antifungal metal based triazole Schiff bases. (1st October 2013) - Chohan, Zahid H.; Hanif, Muhammad
Abstract : A new series of four biologically active triazole derived Schiff base ligands (L 1 –L 4 ) and their cobalt(II), nickel(II), copper(II) and zinc(II) complexes (1 –16 ) have been synthesized and characterized. The ligands were prepared by the condensation reaction of 3-amino-5-methylthio-1 H -1, 2, 4-triazole with chloro-, bromo- and nitro-substituted 2-hydroxybenzaldehyde in an equimolar ratio. The antibacterial and antifungal bioactivity data showed the metal(II) complexes to be more potent antibacterial and antifungal than the parent Schiff bases against one or more bacterial and fungal species.